1994
DOI: 10.5025/hansen1977.63.35
|View full text |Cite
|
Sign up to set email alerts
|

On The Beta-Glucuronidase Binding Protein (BGBP) Of Microorganisms

Abstract: Our previous studies suggested that M. leprae (ML) grow in peripheral nerves and lepra cells because ML metabolize hyaluronic acid (HA), the host with the similar ways to that of ML.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
0
0

Year Published

2005
2005
2005
2005

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 0 publications
0
0
0
Order By: Relevance
“…The main component of culture medium, HA was replaced by its split products, namely glucuronic acid (GA) and N-acetylglucosamine (NAG) (Fig. 2) (28). The reason was that HI-75 can not obtain GA and NAG by enzymatically splitting HA in culture tube since the bacillus can not produce the enzyme which is able to work so (28).…”
Section: On the Hi-75 After The Denials To Be Cultured M Leprae And I...mentioning
confidence: 99%
See 2 more Smart Citations
“…The main component of culture medium, HA was replaced by its split products, namely glucuronic acid (GA) and N-acetylglucosamine (NAG) (Fig. 2) (28). The reason was that HI-75 can not obtain GA and NAG by enzymatically splitting HA in culture tube since the bacillus can not produce the enzyme which is able to work so (28).…”
Section: On the Hi-75 After The Denials To Be Cultured M Leprae And I...mentioning
confidence: 99%
“…2) (28). The reason was that HI-75 can not obtain GA and NAG by enzymatically splitting HA in culture tube since the bacillus can not produce the enzyme which is able to work so (28). As the basis of that reason, histochemical and immunohistochemical studies showed that HI-75 in leproma produce a kind of lectin, which is BGBP (28) and accumulate β-glucuronidase (B-Gase) from host human (Fig.…”
Section: On the Hi-75 After The Denials To Be Cultured M Leprae And I...mentioning
confidence: 99%
See 1 more Smart Citation